2014
DOI: 10.1175/jas-d-13-0349.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Winter Stratospheric Sudden Warming Events and the Seasonal Timing of Spring Stratospheric Final Warming

Abstract: Based on the NCEP–NCAR reanalysis dataset covering 1958–2012, this paper demonstrates a statistically significant relationship between the occurrence of major stratospheric sudden warming events (SSWs) in midwinter and the seasonal timing of stratospheric final warming events (SFWs) in spring. Specifically, early spring SFWs that on average occur in early March tend to be preceded by non-SSW winters, while late spring SFWs that on average take place up until early May are mostly preceded by SSW events in midwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
112
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 42 publications
17
112
0
Order By: Relevance
“…Gerber and Polvani (2009) explicitly demonstrated a realistic tropospheric signal associated with SSWs in their global model. FWs are also observed to have a similar tropospheric impact, although its latitudinal structure differs somewhat from the annular-mode form (Black et al 2006;Black and McDaniel 2007a,b;Hu et al 2014b), and uppertropospheric planetary-scale waves may play a role (Sun et al 2011). Similar results have been found in simplified global models (Sun and Robinson 2009;Sun et al 2011;Sheshadri et al 2014).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Gerber and Polvani (2009) explicitly demonstrated a realistic tropospheric signal associated with SSWs in their global model. FWs are also observed to have a similar tropospheric impact, although its latitudinal structure differs somewhat from the annular-mode form (Black et al 2006;Black and McDaniel 2007a,b;Hu et al 2014b), and uppertropospheric planetary-scale waves may play a role (Sun et al 2011). Similar results have been found in simplified global models (Sun and Robinson 2009;Sun et al 2011;Sheshadri et al 2014).…”
Section: Introductionsupporting
confidence: 54%
“…Both the cases with 3000-and 4000-m wave-2 topography result in weak easterlies following the final warming. Hu et al (2014a), in their analysis of the timing of midwinter warming events and final warming events in the NCEP-NCAR reanalysis, suggested that late spring final warming events tend to be preceded by major SSWs, while early FW events do not. Similarly, in experiment 4, we find that final warming events occur on average 11 days later in years with major SSW events.…”
Section: B Final Warming Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 and 10 SSW events are categorized as Type-1 and Type-25 2, respectively. Hu et al (2014) identified and categorized the SSW events in 55 years of NCEP-NCAR data based on the criteria of CP07. Compared to Hu et al (2014), four SSW events were categorized as different types (the Dec. 1998, Feb. 1999, Jan. 2006, and Feb. 2007.…”
Section: Statistics Of Ssw Events Revealed In Reanalysis Data Sets 20mentioning
confidence: 99%
“…It has long been recognized that the winter to spring transition is characterized by a decay and breakdown of the wintertime westerly jet and its eventual replacement by a zonal mean easterly flow around the polar region. This is known as the stratospheric final warming (SFW) (Hu et al, 2014). It has been observed that certain remnants of wintertime dynamical (Hess, 1990) or chemical tracer features (Orsolini, 2001;Lahoz et al, 2007) can persist well into the summer season.…”
Section: Introductionmentioning
confidence: 99%